Talfīq Mażhab dan Kebutuhannya dalam Fatwa Kontemporer (Telaah atas Pandangan Wahbah al-Zuhailī): The Talfīq of Mażhab and Its Relevance in Contemporary Fatwas (an Analysis of Wahbah al-Zuhailī's Perspectives) - Negara, Muhammad Abduh (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
Talfīq of maẓhab (combining several madhhabs in a single practice) is one of the important issues discussed by fiqh scholars, especially in the last few centuries. Some accept it, while others reject it. Various studies have been presented on this topic by many scholars and researchers. However, in this research, the author tries to connect the issue of talfīq of madhhab with the need for fatwas in the contemporary era and specifically examines the views of Wahbah al-Zuhailī, a very famous contemporary fiqh scholar, on this topic. The research refers to various writings and fatwas from Wahbah al-Zuhailī, then analyzes them based on fiqh, ushul fiqh, and fatwa principles as explained by scholars. Additionally, the author strengthens the analysis by providing examples of fatwas from other contemporary scholars and fatwa institutions, which result in the emergence of talfīq of madhhab. This demonstrates that talfīq of madhhab has been accepted by various groups, even though they sometimes do not mention it explicitly. The results of the research show that Wahbah al-Zuhailī accepts the concept of talfīq of madhhab, with certain conditions, and acknowledges its urgency in fatwas in the contemporary era.